Molecular Modeling of Some Novel 4(3h) - Quinazolinone Derivatives - Patel, Dr. Arun (B R Nahata Smriti Sansthan International Journal of Phramaceutical Sciences & Clinical Research, 2021)
Inhibition of soluble epoxide hydrolase (sEH) is considered as a promising target to reduce blood pressure, improve insulin sensitivity, and decrease inflammation. Material and Method: In this study, a series of some novel quinazoline-4(3H)- one derivatives (3a-t) with varying steric and electronic properties was designed, synthesized, and evaluated as sEH Inhibitors (sEHI). Most of the synthesized compounds had similar inhibitory activity to the commercial reference inhibitor, 12-(3-adamantan-1-ylureido) dodecanoic acid, and among them, 4-chloro-N-(4-(4-oxo-3,4-dihy- droquinazoline-2-yl)phenyl)benzamide (3g) was identified as the most active sEHI (IC50 = 0.5 nM), about two-fold more potent compared to the reference inhibitor. Conclusion: The results of molecular modeling followed by biological studies indicate that a quinazolinone ring serves as a suitable scaffold to develop novel small molecule candidates to inhibits EH and the nature of substituent on the amide moiety has a moderate effect on the activity.